Tourist Safety Level in Cengklik Reservoir: Impact and Development Strategy to Increase Tourist Attraction - Made Pradipta (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
Cengklik Reservoir tourist attraction is the latest tourist attraction in Boyolali. By relying solely on artificial tourism, Cengklik Reservoir transformed itself from rarely visited to many visitors not only anglers. The problem is the lack of facilities for security, infrastructure, facilities, and adequate infrastructure so that tourists feel uncomfortable. Therefore, the purpose of this research is to analyze and evaluate the activities at Cengklik Reservoir. This research uses a qualitative method with a descriptive approach so that it can identify the shortcomings that exist in the Cengklik Reservoir tourist attraction. The results found that the tourist activity there is a boat ride around the reservoir. In the research it was found that the activity was not equipped with buoys and the lack of adequate facilities and infrastructure made tourists feel unsafe. This study provides recommendations for improvements in terms of rescue facilities such as buoys, adequate facilities and infrastructure, and human resources (HR) who are ready in the event of a disaster.